Factores de riesgo que influyen en la desnutrición en preescolares de la Parroquia El Salto, Babahoyo, octubre 2024- mayo 2025. - Pérez Sola, Nancy Elizabeth (2025)
Childhood malnutrition is the result of insufficient food intake in quantity and quality, this condition causes delay in the growth and development of the preschooler that occurs due to various factors. Objective: To determine the risk factors that influence malnutrition in preschoolers of the El Salto Parish, Babahoyo, October 2024-May 2025. Methodology: The inductive-deductive method, quantitative modality, observational design, descriptive, field and cross-sectional type were used. The survey was applied as a technique through a questionnaire made up of 14 questions. The population was 44 children aged 3-5 years. Results: It was obtained that the most frequent age was 4 years with 56.8%, followed by 5 years with 27.3%; Among the risk factors, the male gender (56.8%), maternal age of 20-24 years (52.3%), primary education level (47.7%), low socioeconomic level (54.5%), were housewives (43.2%), annual medical care of their child (72.7%), vaccination schedule up to date (52.3%), consumption of healthy foods a few times a month (72.7%) and occasionally receiving advice on healthy eating and prevention of malnutrition (59.1%) stood out; and the predominant degree of malnutrition was mild in 59.1%. Conclusion: There are biological, socioeconomic, cultural and nutritional risk factors related to the incidence of malnutrition in preschool children in the El Salto parish.